Light Exposure in Young University Students: Effect on Ocular Surface Health: Doi: 10.36351/pjo.v40i3.1834 - Awad Alkozi, Hanan (Pakistan Journal of Ophthalmology, 2024)
Purpose: The ocular surface is the first structure to absorb light and transfer it to retina to form images. However, the effect of different wavelengths and light exposure timing could harm the eye. The current study aims to measure light exposure and its correlation to the ocular surface. Study Design: Cross sectional observational. Place and Duration of Study: Qassim University, from March to September 2023. Methods: Light sensor buttons (RGB) were used in the current study (LYS technologies); 53 subjects were asked to wear them on the collar for one week, followed by a visit to the optometry clinic for an eye examination by bio-microscopy and Schirmer I test. Consequently, readings from Kerato-graph 5M were obtained. Lastly, participants were asked to fill out a validated Arabic OSDI questionnaire. Results: Results of the dry eye symptoms scale revealed that 24.5% had mild symptoms, and 20.8% of participants reported severe dry eye symptoms. A negative correlation between the Schirmer test and OSDI scores was found. Blue light exposure at night was negatively correlated to tear meniscus height (P <0.05). Moreover, tear meniscus height was lower in participants with higher exposure to the red component of light during the day and higher melanotic lux in the daytime (P<0.05). Tear breakup time was lower in patients exposed to higher melanopic lux during nighttime (p<0.05). Conclusion: Light exposure habits are associated with some dry eye parameters. Moreover, light at night, especially melanopic lux wave-length is a risk factor for developing dry eye disease.